Development of pulsed current gas tungsten arc welding technique for dissimilar joints of marine grade alloys. (January 2016) - Devendranath Ramkumar, K.; Naren, Shah Vitesh; Karthik Paga, Venkata Rama; Tiwari, Ambuj; Arivazhagan, N.
Graphical abstract: PCGTA weldment employing (a) ERNiCu-7 and (b) ERNiCrMo-4 filler. Highlights: Weldability of Monel 400 and AISI 904L using PCGTA welding employing ERNiCu-7 and ERNiCrMo-4. Improved joint strength for ERNiCu-7 weldments. Formation of partially melted zone at the HAZ of Monel 400 while using ERNiCrMo-4. Abstract: This research study articulates the joining of marine grade alloys Monel 400 and AISI 904L by pulsed current gas tungsten arc welding (PCGTAW) technique using ERNiCu-7 and ERNiCrMo-4 filler metals. Experimental studies were carried out to establish the structure–property relationships of the dissimilar weldments. Microstructure studies corroborated the formation of migrated grain boundaries at the fusion zone of ERNiCrMo-4 weldments. Also a partially melted zone (PMZ) was observed at the weld interface of Monel 400 while using ERNiCrMo-4 filler. Tensile studies corroborated that the joint strength was found better for the ERNiCu-7 weldments compared to ERNiCrMo-4 weldments. Tensile failures occurred at the HAZ of Monel 400 for ERNiCrMo-4 weldments which could be reasoned out to the presence of partially melted zone (PMZ). Charpy V-notch studies demonstrated that both the weldments absorbed higher amount of energy by showing ductile mode of fracture. The outcomes of the present study will be beneficial to the industries operating these metals.